Low-humidity sensing properties of multi-layered graphene grown by chemical vapor deposition - Duesberg, Georg (My University, 2020)
Humidity sensing is fundamental in some applications, as humidity can be a strong interferent in the detection of analytes under environmental conditions. Ideally, materials sensitive or insensitive towards humidity are strongly needed for the sensors used in the first or second case, respectively.We present here the sensing properties of multi-layered graphene (MLG) upon exposure to differentlevels of relative humidity. We synthesize MLG by chemical vapor deposition, as shown by Ramanspectroscopy, Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM). Throughan MLG-based resistor, we show that MLG is scarcely sensitive to humidity in the range 30%–70%,determining current variations in the range of 0.005%/%relative humidity (RH) well below the variationinduced by other analytes. These findings, due to the morphological properties of MLG, suggestthat defective MLG is the ideal sensing material to implement in gas sensors operating both at room temperature and humid conditions.
Keywords: Graphene; Defects; Humidity; Chemical vapor deposition; Sensitivity; Sensors